Chest X-ray image quality assessment in a pediatric cardiac intensive care unit. (April 2023) - Martire, F.; Polito, C.; Ciucci, D.; Solfaroli Camillocci, E.; Longo, M.; Genovese, E.; Cirillo, M.; Tomà, P.; Magistrelli, A.; Cannatà, V.
Abstract: Background: Patients admitted to cardiac intensive care unit (CICU) are daily monitored through radiographic examinations. A clinically and diagnostically acceptable image quality is characterized by the visualization of the anatomical structures in absence of artefacts, good contrast and ability to answer the clinical question. However, the exam involves a patient exposure at X-ray that has to be minimized for radioprotection reasons, especially in childhood. Objective: Goal of the study was the image quality evaluation and the entrance surface air kerma (Ke ) estimation of the radiological investigations for children admitted at CICU. Materials and methods: The study was conducted on 105 chest radiographs of children admitted to CICU, with age ranging from 0 to 5 years and classified into three age groups. Results: In the images assessment, all the exams resulted suitable to answer the clinical task. The absence of artefacts was observed and the image quality criteria were met for most part of the exams. Contrary, the collimation was not respected, especially the lateral one Concerning the Ke, it resulted lower than the reference value of 50 μGy for all the cases in study. Conclusion: Radiographic images acquired at CICU meet the image quality requirements; in particular, good visualization of the anatomical structures in absence of artefacts, high contrast and ability to answer the clinical task. The radiation exposure of the patient resulted low and compatible with a large number of radiographic examinations, which may be requested for patients during the hospitalization period. Highlights: Approach for assessing image quality based on the visibility of anatomical features. Image evaluation based on criteria optimize medical imaging with ionizing radiation. Exposure technique identification to ensure image quality with minimal radiation dose. Artifact and collimation analysis avoid poor quality images that can impair diagnosis.